Las destrezas motrices en el desarrollo de las capacidades intelectuales de los niños de primero, segundo y tercer año de educación básica de la escuela fiscal mixta “Tulcán” del recinto la Esmeralda - cantón Montalvo - provincia de Los Ríos, año lectivo 2010 - 2011. - Alpala Cuaspud, Hilda María (2011)
To recognize the importance of forming a solid motive base in the children that allow to the develop their activities projecting with success in the children a full development and full with satisfaction. For such a reason we chose this topic focusing us in area of the motricidad in the Mixed Fiscal School "Tulcán", we detect the little one he/she practices of the motive dexterities in the intellectual development of the children. Reason for which take as starting point at the primary level, focusing us in the Initial Education in the First Year of Basic Education. We expect in this way that the present investigation carried out in this area is a firm base for other projects that have the vision of change and development of the future generations They are several the interpretations developed around the acquisition and control of the movement, from the positions more analytics to those considered more global or more integrative. Certain conceptions on the motricidad like the sport initiation, the training, the treatment of relating contents to the physical condition and, even, the psicomotricidad, they have made focuses or interpretations of the movement based in perspectives behaviorists of the same one to proliferate. At the present time, we should understand the processes of acquisition and control of the movement from a conception more cognitive and global since the motricidad in these ages cannot be isolated of the different environments of the behavior of people, and much less not to keep in mind the didactic positions that the current educational system postulates. In this global position of the motricidad it also charges special relevance the neurological interpretation of the motricidad that defends that the activity of the children is eminently perceptive-motive. Finally, the motive perception based on the prosecution of the information is another of the pillars to interpret the acquisition and the control of the movement. The pattern of learning motor, based on the theories of the prosecution of the information, it guides toward the establishment of sequences adapted to the different phases of the learning. The selective perception of the outstanding stimuli, the progressive construction of answer outlines and the development of the strategies of decision among different alternatives to get their objectives constitute the rules for a logical sequence of the learning’s motors. A current conception and globalizadora of the motricidad should consider the incidence that each one of these interpretations has in the acquisition and the control of the movement. The conjunction of the neurological one, the evolutionary one and that of prosecution of the information should meet in a conception cognitive of the motricidad.